Exenatide protects against hypoxia/reoxygenation-induced apoptosis by improving mitochondrial function in H9c2 cells. (April 2014) - Chang, Guanglei; Zhang, Dongying; Liu, Jian; Zhang, Peng; Ye, Lin; Lu, Kai; Duan, Qin; Zheng, Aihua; Qin, Shu
Glucagon-like peptide-1 (GLP-1) analogues might exert the cardioprotective effects via attenuating apoptosis. This study aimed to determine the protective effects and mechanism of exenatide, a GLP-1 analogue, on cardiomyocyte apoptosis using an in vitro model of hypoxia/reoxygenation (H/R). H9c2 cells were employed to establish an in vitro model of H/R. 200 nM exenatide pretreatment significantly reduced apoptosis measured by flow cytometry. To further study the antiapoptotic mechanism of exenatide, we used flow cytometry in combination with laser confocal microscopy to determine the interaction between exenatide and the process of mitochondria-mediated apoptosis. We found that exenatide pretreatment reduced the intracellular reactive oxygen species (ROS) levels and decreased the mitochondrial calcium overload caused by H/R. Furthermore, an increase of total superoxide dismutase (T-SOD) levels, a decrease of malondialdehyde (MDA) levels, a preservation of mitochondrial membrane potential (ΔΨm), a reduction of cytochrome-c release, a decline of cleaved caspase-3 expression, and caspase-3 activation were observed in exenatide-pretreated cultures. These results suggest that exenatide exerts a protective effect on preventing against H/R-induced apoptosis. Importantly, the protective effects of exenatide may be attributed to its role in improving mitochondrial function in H9c2 cells subjected to H/R.